Experimental assessment of forest flammability after selective logging in the Brazilian Amazon - Manoela S. Machado; Matthew G. Hethcoat; Marcia N. Macedo; Carlos A. Peres; David P. Edwards (Communications Earth & Environment)
Abstract Tropical forests, strongholds of biodiversity and carbon storage, face increasing threats from selective logging and fires. Selective logging disrupts forest structure, leaving canopy gaps where commercially valuable trees once stood, potentially increasing fire susceptibility through heating and drying understorey microclimates and altering fuel conditions. Here, we empirically examine the effects of selective logging on microclimate and flammability in the Brazilian Amazon. Using a controlled fire experiment during the first dry season post-harvest, we found that logging gaps were hotter and drier than surrounding forests, with larger gaps showing steeper temperature gradients. Leaf-litter moisture, a strong predictor of ignition, was modestly lower in gap centres. Despite this spatial variability in fuel moisture, the propensity of fuels to catch and sustain fires consistently increased as the dry season advanced, suggesting the selectively logged mosaic may be uniformly vulnerable to fire once exposed to ignition sources. These findings suggest that selective logging does not act alone in driving fire risk, with seasonal drying and ignition sources also contributing to increased vulnerability. These results highlight the importance of ignition suppression in post-logging management of forests that continue to hold substantial conservation value, including biodiversity and ecosystem services, as dry seasons intensify under climate change.